Autoimmune Epilepsy: The Evolving Science of Neural Autoimmunity and Its Impact on Epilepsy Management - Quek, Amy M.L.; O'Toole, Orna (Seminars in Neurology, 2018)
Autoimmune epilepsy is increasingly recognized as a distinct clinical entity, driven in large part by the recent discovery of neural autoantibodies in patients with isolated or predominant epilepsy presentations. Detection of neural autoantibodies in high-risk epilepsy patients supports an immune-mediated cause of seizures and, if applicable, directs the search for an underlying cancer when the paraneoplastic association of the associated antibody is compelling. Early diagnosis of autoimmune epilepsy is crucial, as prompt initiation of immunosuppressive treatment increases the likelihood of achieving either seizure freedom or a substantial reduction in seizure frequency. A practical clinical approach that incorporates risk scores to guide patient selection on the basis of clinical features, neural autoantibodies, and a treatment trial of immunotherapy is suggested. Elucidating an immunological basis of epilepsy provides neurologists with wider treatment options (incorporating immune-suppressive treatment), in addition to standard antiepileptic drugs, which often improves patient outcomes.
Keywords: autoimmune; epilepsy; encephalitis; seizures; antibodies